INTEREST IN LEARNING SCIENCE SUBJECTS AMONG STUDENTS AT SMP AN-NAHLU KISARAN - Ilma, Zizni; Nasution, Dara Sumaiya; Tambunan, Muhammad Iqbal H; Saragih, Sisca Sri Dewi; Sari, Dewi Sartika (Jurnal Pelita Pendidikan, 2025)
This study aims to describe the learning interest of An-Nahlu Kisaran Junior High School students in Natural Sciences (IPA). This study uses a qualitative approach with a descriptive method. The research population consisted of all 144 students in grades VII and VIII (5 classes). Data was obtained through a closed questionnaire that measured aspects of learning interest, including feelings of enjoyment, interest, attention, and student participation in science learning. The results of the study show that the majority of students have a good interest in learning, with an average score of 166.0. The results show that 11% (9 students) are very interested, 38% (31 students) are interested, 30% (25 students) are quite interested, 16% (13 students) are less interested, and only 5% (4 students) are not interested in science subjects. Based on gender, there was no difference between the two. Male and female students had the same level of interest in science subjects. Internal factors, such as motivation, curiosity, and attention, as well as external factors, such as support from family, school, and environment, influenced students' level of interest in learning. From the results of this study, it can be said that the learning environment at SMP An Nahlu has supported the development of students' interest in science subjects.